Current state of methods for low–dense constructional composite materials producing (overview) - Shcherbakova, E.P.; Prokhorova, A.D.; Karpenko, A.V.; Yanko, T.B. (Вопросы атомной науки и техники, 2020)
The analysis of existing methods for imparting a porous structure to structural composite materials is carried out. In particular, the introduction and subsequent removal of the filler, the addition of foaming agents or separately prepared foam to the suspension, as well as gas formation. Discloses a method of introducing into the material of the hollow microspheres, which finds use in the development of thermal barrier composites. The introduction and subsequent carbonization of additives is considered. A method for producing highly porous carbon-graphite materials with a uniformly distributed pore structure using isostatic pressing with pyrocarbon in the form of a binder is considered. Describes the receipt as highly porous carbon materials of foam coke based on carbon microspheres, carbon materials based on fibers, pressed carbon black, porous pyrocarbon and related materials, as well as porous glassy carbon. Виконано аналіз існуючих методів надання конструкційним композиційним матеріалам пористої структури, зокрема, введення і подальше видалення наповнювача, додавання до суспензії піноутворювачів або окремо приготовленої піни, а також газоутворення. Описано метод введення в матеріал порожнистих мікросфер, який знаходить застосування при розробці теплозахисних композиційних матеріалів. Розглянуто введення і подальша карбонізація добавок. Розглянуто метод отримання високопористих вуглеграфітових матеріалів з рівномірно розподіленою структурою пор з використанням ізостатичного пресування з піровуглецем у вигляді сполучного. Описано одержання в якості високопористих вуглецевих матеріалів пінококсів на основі вуглецевих мікросфер, вуглецеві матеріали на основі волокон, пресованої сажі, пористого піровуглецю і пов’язаних ним матеріалів, а також пористого скловуглецю. Выполнен анализ существующих методов придания конструкционным композиционным материалам пористой структуры, в частности, введение и последующее удаление наполнителя, добавление к суспензии пенообразователей или отдельно приготовленной пены, а также газообразование. Описан метод введения в материал полых микросфер, который находит применение при разработке теплозащитных композиционных материалов. Рассмотрены введение и последующая карбонизация добавок, а также метод получения высокопористых углеграфитовых материалов с равномерно распределенной структурой пор и использованием изостатического прессования с пироуглеродом в виде связующего. Описано получение в качестве высокопористых углеродных материалов пенококсов на основе углеродных микросфер, углеродных материалов на основе волокон, прессованной сажи, пористого пироуглерода и связанных им материалов, а также пористого стеклоуглерода.